Using Digital Stories in Reading Class: : the New Literacy for Young Learners in 21st Century - Brigitta Septarini Rahmasari (UIBU, 2023)
Reading achievement and willingness to get involved in reading activities among young learners are affected by their reading motivation and the texts they select for reading. Since there is software that makes stories readable on personal devices, using digital stories in the classroom is one of the strategies to promote reading skills and students' motivation to read. The purposes of this research are to know the implementation of digital stories in teaching reading to young learners and to know the advantages and disadvantages of the use of digital stories in teaching reading to young learners. This research uses a qualitative method. To collect the data, the researcher uses observation and interviews. Meanwhile, to analyze the data, the researcher uses data reduction, data display, and drawing conclusions. The results show that students can use digital stories easily. They click the link given by the teacher and choose the stories they like on the website. Some interesting features can be added to story content while they are reading the text, such as interactive exercises, quizzes, and discussions that are not available in the printed text. The strengths are that digital stories are used as an interesting learning tool, particularly for students who are accustomed to technology, and help young readers enhance their literacy skills and motivation. The weaknesses are the internet connection is sometimes unstable so the students are difficult to access the stories and no quiz menu in the website. It makes the students not challenged to read it at home